Using Storm for scaleable sequential statistical inference - WILSON, SIMON (My University, 2014)
This article describes Storm, an environment for doing streaming data analysis. Two examples of sequential data analysis | computation of a running summary statistic and sequential updating of a posterior distribution | are implemented and their performance is investigated.
Proceedings of CompStat 2014
CompStat 2014
PUBLISHED
Geneva
Keywords: streaming data; sequential inference; Storm,; Smart & Sustainable Planet; Distributed systems; Sequential data analysis; Statistical computing